A Bio-Inspired, Self-Healing, Resilient Architecture for Digital Instrumentation and Control Systems and Embedded Devices. (3rd June 2018) - Khairullah, Shawkat S.; Elks, Carl R.
Abstract: One of the essential concepts being postulated for next generation nuclear power plants (NPPs) that could include Gen IV reactors—small modular reactors—is the notion of resilient and survivable instrumentation and control (I&C) systems. Resilience at the system and plant level will rely on highly robust and fault-tolerant digital embedded devices as a foundation. This paper presents a new self-healing programmable digital I&C architecture, BioSymPLe, inspired from the way nature responds, defends, and heals: the stem cells in the immune system of living organisms and the pathway from DNA to protein. The BioSymPLe is organized in a four-layered approach: (1) cellular layer that includes four sublayers, with each sublayer allocating two functional B cells which represent the building block that executes the local functionality of NPP critical application based on the expression for DNA genetic codes stored inside each cell; (2) tissue layer that embeds eight redundant T cells and eight routing units to facilitate coordination and organized behavior among a network of four cellular sublayers; (3) internal healing layer that monitors the correct execution of functions at the cellular level and activates healing mechanism at the tissue level; and (4) external healing layer using a concept of embryonic stem cells by differentiating this type of cell to repair the faulty T cells. Finally, the BioSymPLe is capable of tolerating a significant number of faults (transient, permanent, or hardware common cause failures) that can stem from environmental disturbances, and we believe it can positively impact the operation of next generation digital I&C systems in NPPs.